Effects of early life adverse experiences on the brain: implications from maternal separation models in rodents - Nishi, Mayumi; Horii-Hayashi, Noriko; Sasagawa, Takayo (Frontiers in Neuroscience, 2014)
During postnatal development, adverse early life experiences can affect the formation of neuronal circuits and exert long-lasting influences on neural function. Many studies have shown that daily repeated MS, an animal model of early life stress, can modulate the hypothalamic-pituitary-adrenal axis (HPA axis) and can affect subsequent brain function and emotional behavior during adulthood. However, the molecular basis of the long-lasting effects of early life stress on brain function has not been completely elucidated. In this review, we introduce various cases of MS in rodents and illustrate the alterations in HPA axis activity by focusing on corticosterone (CORT), an end product of the HPA axis in rodents. We then present a characterization of the brain regions affected by various patterns of MS, including repeated MS and single time MS at various stages before weaning, by investigating c-Fos expression, a biological marker of neuronal activity. These CORT and c-Fos studies suggest that repeated early life stress may affect neuronal function in region- and temporal-specific manners, indicating a critical period for habituation to early life stress. Next, we discuss how early life stress can impact behavior, namely by inducing depression, anxiety or eating disorders. Furthermore, alterations in gene expression in adult mice exposed to MS, especially epigenetic changes of DNA methylation, are discussed.